Assessing social media marketing activities and customer equity activities influencing customer loyalty to clothing thrifting in Yogyakarta - Aditya Ainurrisqi Rais; Anas Hidayat (Institute of Computer Science (IOCS), 2022)
Marketing activities using social media have been carried out by providers of products, goods, and services to attract consumers. However, there have not been many studies that measure social media marketing activities and customer equity activities regarding value equity and relationship equity and their impact on customer loyalty. This study analyzes the influence of social media marketing and customer equity activities on loyalty to thrifting clothing in Yogyakarta. Design quantitative research with a statistical approach. The study was conducted by distributing questionnaires to respondents focused on consumers of thrifted clothing in Yogyakarta, with as many as 332 respondents using a google form. The research sample was determined by convenience sampling. Analysis of data using a structural equation model with AMOS. The results show that social media marketing has a significant influence on value equity (p= 0.000), customer loyalty (p= 0.011), and relationship equity (p= 0.000), while customer loyalty is significantly influenced by value equity (p= 0.000) and relationship equity (p= 0.000). Hence, social media marketing and equity activities significantly affect customers loyalty to clothing thrifting in Yogyakarta.